chứng tỏ (a-b+c) – (a+c)= -b (a+b)-(b-a)+c=2a+c

Question

chứng tỏ
(a-b+c) – (a+c)= -b
(a+b)-(b-a)+c=2a+c

in progress 0
Adalynn 2 tuần 2021-07-12T12:30:01+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-07-12T12:31:35+00:00

    Vế trái:

    =(a-b+c) – (a+c)

    =a-b+c-a-c=0

    =-b=VP

    ⇒đpcm

    0
    2021-07-12T12:31:37+00:00

    Ta có:

    VT = $ (a-b+c) – (a+c)$

         = $a-b+c -a-c$

         = $(a-a)+(c-c)-b$

         = $ 0 + 0 -b$

         = $ -b=$ VP

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )